A new species of Mazosia (lichenised Ascomycetes : Roccellaceae ) from Tasmania - Gintaras Kantvilas (Plant and Fungal Systematics, 2020)
Two species of Mazosia occur in Tasmania: the foliicolous, pantropical M. phyllosema and M. corticola , here described as new to science. The new species is characterised by a corticolous thallus containing psoromic acid and three-septate ascospores, 17–27 × 4–6.5 μm; it occurs in Tasmanian and Victoria.